A - Twain, Mark (Oxford University Press, 2001)
Starters are an introductory level to the new Oxford Bookworms Library, suitable for readers in their first or second years of learning English. The Starters series are original stories in a variety of formats: narrative, interactive, and comic strip. They contain glossaries and exercises and are carefully graded in structure and vocabulary. Cassettes are available for some titles